In Vivo Antithrombotic Potential of Protease From Bacillus Thuringiensis HSFI-12 - Dewi, Okta Yosiana; Zilda, Dewi Seswita; Rakhmawatie, Maya Dian; Samiasih, Amin; Ethica, Stalis Norma (Scripta Medica, 2023)
Background/Aim: Cardiovascular disease (CVD) is the primary non-communicable disease at the global level due to abnormal platelet aggregation by fibrin forming clots in blood vessels called thrombus. The search for thrombolytic drugs is largely carried out to treat thrombosis. Crude extract and dialysate protease of Bacillus thuringiensis HSFI-12 is known to have thrombolytic activity in vitro. The in vivo thrombolytic activity evaluation of concentrated protease of the bacterium is yet to be done. This study aimed to evaluate in vivo thrombolytic activity of concentrated protease produced by ultrafiltration of crude B thuringiensis HSFI-12 protease using Rattus norvegicus as animal model. Methods: Carrageenan was used as thrombosis induction agent in rats. Intravenous injection of B thuringiensis HSFI-12 concentrated protease doses of 75, 150, 300, 600 µg/kg BW was administered to rats, then induction of carrageenan was given intravenously to the rats’ tails 30 min after injection of B thuringiensis HSFI-12 protease concentrate. The average length of the infarct area in the tail of the rat was shorter in the rats that were given various doses of B thuringiensis HSFI-12 protease concentrate compared to the negative control (rats induced by carrageenan 20 mg/kg BW). Results: The PT examination results showed a prolonged PT time at 300 µg/kg BW dose, while there was at risk of bleeding at 600 µg/kg BW dose. The activated partial thromboplastin time (aPTT) examination results showed that time elongation beyond the normal range did not occur in rats after treatment. The amount leukocytes (WBC) and erythrocytes (RBC) after treatment were within the normal range indicating that they did not affect the haemostasis mechanism, while the platelet count (PLT) assay showed decrease in the number of platelets (thrombocytopenia). However, after treatment the number of platelets (PLT) showed a positive response as seen from an increase in values close to normal range. As conclusion, induction of carrageenan conducted had successfully caused thrombosis in R norvegicus’ tail used as the thrombosis model. Conclusion: Concentrated protease of B thuringiensis HSFI-12 showed in vivo antithrombotic potential with an effective dose of based on PT, aPTT and blood count evaluation at 150 µg/kg BW.